The Decrease in FlaA Observed in a flaB Mutant of Borrelia burgdorferi Occurs Posttranscriptionally - Motaleb, M. A. (American Society for Microbiology, 2004)
The Lyme disease bacterium Borrelia burgdorferi is a motile spirochete with a flat-wave morphology. The periplasmic flagella, which are situated between the outer membrane sheath and cell cylinder, are essential for both the cell's wavy shape and motility. Here we focus on the structure and regulation of its periplasmic flagella. Previous studies have suggested that the periplasmic flagella consist of a polymer of the major filament protein FlaB and a minor protein, FlaA. We used immunoprecipitation methodology to present further evidence that FlaA is indeed a flagellar protein. In addition, in contrast to FlaA of the spirochete Brachyspira hyodysenteriae, B. burgdorferi FlaA did not impact the overall helical shape of the periplasmic flagella. We have previously shown that B. burgdorferi lacks the sigma factor-dependent cascade control of motility gene transcription found in other bacteria. To begin to understand motility gene regulation in B. burgdorferi, we examined the effects of an insertion mutation in flaB on the amounts of proteins encoded by motility genes. Of several motility gene-encoded proteins examined, only the amount of FlaA was decreased in the flaB mutant; it was 13% compared to the wild-type amount. Real-time reverse transcriptase PCR analysis indicated that this inhibition was not the result of a decrease in flaA mRNA. In addition, protein stability analysis suggested that FlaA was turned over in the flaB mutant. Our results indicate that the lack of FlaB negatively influences the amount of FlaA found in the cell and that this effect is at the level of either translational control or protein turnover.